1995
DOI: 10.1029/94ja02702
|View full text |Cite
|
Sign up to set email alerts
|

Low‐altitude observations and modeling of quasi‐steady magnetopause reconnection

Abstract: Data from two near‐conjugate passes of DE 1 and DE 2 through the cusp/cleft region of the Earth's magnetosphere are presented and compared with model calculations of particle transport from the solar wind to spacecraft locations in the magnetosphere. Comparison of the observed and calculated particle spectra shows that the model can successfully match the spectra at both spacecraft using the same model parameters. This demonstrates that the modeling technique is applicable at both high and low altitudes. We ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 35 publications
6
73
0
Order By: Relevance
“…It is necessary to maintain change neutrality. Onsager et al (1995) have noted the importance of the ionospheric source of electrons in maintaining charge neutrality. We also noted that recently small uxes of very energetic ions ($200 keV) have been detected by the POLAR satellite on open cusp-like ®eld lines (Spence, private communication).…”
Section: Implications and Interpretation Of The New Observationsmentioning
confidence: 99%
“…It is necessary to maintain change neutrality. Onsager et al (1995) have noted the importance of the ionospheric source of electrons in maintaining charge neutrality. We also noted that recently small uxes of very energetic ions ($200 keV) have been detected by the POLAR satellite on open cusp-like ®eld lines (Spence, private communication).…”
Section: Implications and Interpretation Of The New Observationsmentioning
confidence: 99%
“…For example, the merging process has been believed to be quasistationary (e.g. Onsager et al, 1995;Fuselier et al, 2000;Frey et al, 2002Frey et al, , 2003Chang et al, 2004), while Chisham et al (2004) noted reconnection potential with transient enhancements. Lu et al (2004) observed intermittent magnetic reconnection at the high-latitude magnetopause, and Provan et al (2005) suggested that the dayside reconnection rate was modulated by variations in the solar wind dynamic pressure and the IMF B z component.…”
Section: ∼30 • -40mentioning
confidence: 99%
“…While statistical plasma properties of the LLBL and cusp regions have been extensively studied (e.g., Smith and Lockwood, 1996;Meng, 1988, 1992;Onsager et al, 1995;Lockwood and Smith, 1994;Lockwood et al, 1998;Aparicio et al, 1991;Newell et al, 1991a,b;Lundin, 1992, 1993;Zhou et al, 2000), the electron edge of the LLBL containing only magnetosheath-like electrons is a comparatively poorly studied region. However, Wing et al (1996) and Wing et al (2005) modelled the penetration of the magnetosheath electrons to low altitudes and compared results from these models with DMSP observations.…”
Section: Introductionmentioning
confidence: 99%